A protocol to secure context-aware service discovery in complex earth experiments - Carmo, Ricardo R.M. do; Costa, André Cypriano Monteiro; dos Santos, José Laurindo Campos; Filho, José Gonçalves Pereira (Environmental Science and Engineering (Subseries: Environmental Science), 2007)
Ubiquitous Computing allows the use of context-aware applications, a new set of functionalities which adopt contextual information. The structure of such type of information allows the development of more flexible and adaptable services, rich in functions and centered on user demands. The development and management of such services require dynamic mechanisms which consider the nature of contextual information. Service discovery protocols offer such dynamism and ontology is a way to deal with the complexity of the contextual information. Experiments to monitor the environment, like the LBA, due to the diversity of devices, services and contexts, are good examples of ubiquitous environments where service discovery protocols can be a essential tool. SCaSDP is a new service discovery protocol which considers the nature of contextual information and allows a secure management of services and user information. SCaSDP uses a semantic matching algorithm of service descriptions based on ontology's.
Keywords: Environmental Engineering; Experiments; Information Services; Ubiquitous Computing; Context Aware Applications; Context Aware Services; Contextual Information; Dynamic Mechanism; Semantic Matching; Service Description; Service Discovery Protocol; Ubiquitous Environments; Information Technology